The Effect of Tariffs, Existence of Internal Control Committee, and Number of Customers on the Performance of Regional-Owned Water Supply Company (PDAM) In Indonesia - Muhammad Khaidir Arief (Politeknik Keuangan Negara STAN, 2024)
Based on data from the Ministry of Public Works and Public Housing (PUPR), the majority of Indonesian Regional-Owned Water Supply Company (PDAM) during the financial year of 2019 to 2022 did not show any improvement in performance as indicated by experiencing losses and projected to experience bankruptcy if not managed well. This research aims to examine the effect of tariffs, the existence of an Internal Control Committee, and the number of customers on the performance of PDAMs in Indonesia with firm size as a control variable. In this research, the type of data used is secondary data and is prepared using quantitative research methods using panel data. This research used a sample of 385 PDAMs with a total research period of four years. The results of the research conducted explain that tariffs have a negative and significant relationship to PDAM performance, while the existence of Internal Control Committee and the number of customers have a positive and significant relationship to PDAM performance. This research shows that PDAMs need to review the tariffs, reduce water loss levels, form Internal Control Committee, increase the number of customers, and record and reclassify customers to improve company performance.